The crusades - Jaspert, Nikolas (Taylor and Francis, 2006)
Book Cover; Half-Title; Title; Copyright; Contents; Author's foreword; Author's foreword to the English edition; 1 The background; 2 The crusades in the Near East; 3 The crusader lordships; 4 The European crusades; 5 The military religious orders; 6 The aftermath; Select bibliography; Index
Description based upon print version of record
Keywords: Electronic books; Geschichte; Kreuzzüge